PENGARUH KEPEMILIKAN ASING DAN KEPEMILIKAN PEMERINTAH TERHADAP AGENCY COST PADA PERUSAHAAN YANG LISTING DI BEI TAHUN 2008 - 2013 - Panuju, Humosor Panuju; ', Makhdalena; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted to investigate the effect of foreign ownership and government ownership of the Agency Cost. Population of this research is all companies listed on the Indonesia Stock Exchange that has the necessary data (foreign ownership and possession of the governments) 6 consecutive years - participated (2008-2013). Data used is secondary data. Data analysis technique using multiple regression analysis. The result showed that the Government Ownership Foreign Ownership and simultaneously influence the Agency Cost of 0.481. Furthermore, the partial results of the study showed an effect on Agency Foreign Ownership Cost of 0.426409. Government ownership influence the Agency Cost of 0.83905. Keywords: Foreign Ownership, Government Ownership and Agency Costs